Diseño de un sistema de información para el mantenimiento de la bomba REDA HPS estación M-14 campo Tibú Norte de Santander - Pinto Torrado, Fabian Arturo (Universidad Antonio Nariño, 2023)
The main objective of the project was to design an information system for the maintenance of the Reda HPS Pumps Station M-14 Campo Tibú. Optimization is achieved in the crude producing wells that comprise the M-14 sector and that depend on this water injection, as well as optimizing the maintenance plans that have been developed for this particular equipment, achieving that the useful life and better performance by lowering the chances of failure. The creation of this project is based on the collection of information directly from the field to people who have been directly related to the maintenance of the equipment, seeking with this to unify criteria and improve the way of carrying out maintenance.